Krisis Perlindungan Anak dengan HIVAIDS di Indonesia Rechtvacum dan Dampaknya Terhadap Hak Hak Dasar - Oktavia, Enika Maya (Jurnal Ilmiah Widya Sosiopolitika, 2025)
To addresses the serious legal protection issues faced by children living with HIV/AIDS in Indonesia. The legal vacuum directly affects their basic rights, such as access to education, healthcare, and protection from discrimination. Although Indonesia has child protection laws, the absence of specific regulations for children with HIV/AIDS leaves them vulnerable to deep-rooted social stigma. This research employs normative and qualitative approaches to deeply explore how this legal gap exacerbates the lives of these children. The findings emphasize the urgent need for inclusive legal reforms and intensive educational efforts to dismantle societal stigma. This study presents bold recommendations to foster a more inclusive environment and ensure stronger protection for children with HIV/AIDS, paving the way for more humane and progressive policies in Indonesia.